(untitled) (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Objective: The problem of creating effective labour productivity is relevant for public and private sector organisations due to market volatility and determines important in addition to the introduction of optimal tools in the working process, the creation of the favourable environment in the staff team and as a consequence of the prevention of emotional burnout among employees. Background: In conditions of social and economic instability in the CIS countries and competition in the labour market in a wide range of specialities, it leads to the increase of competencies and requirements for employees of the industry, and as a consequence increases their responsibility to the society. Method: A retrospective research method was applied to identify cause-and-effect relationships and patterns between all components of the phenomenon of emotional burnout in the labour process. Results: In the course of the research, a standardised Professional Burnout questionnaire was used. Also, criteria and a grading scale were identified, the results processed using statistical methods in the SPSS 17 data processing programme. Conclusion: On the basis of the results of the research conducted, practical recommendations were formulated, the implementation of which will help reduce the level of emotional burnout among employees of the organisation